In vitro testing of a funnel-tip catheter with different clot types to decrease clot migration in mechanical thrombectomy - Payne, Emily Sarah; Krost-Reuhl, Samantha; Heimann, Axel; Keric, Naureen; Masomi-Bornwasser, Julia; Gerber, Tiemo; Seidman, Larissa; Kirschner, Stefanie; Brockmann, Marc Alexander; Tanyildizi, Yasemin (Interventional neuroradiology, 2023)
Background - Mechanical thrombectomy is the standard treatment for acute ischemic stroke in patients with large vessel occlusion and can be performed up to 24h after symptom onset. Despite high recanalization rates, embolism in new territories has been reported in 8.6% of the cases. Causes for this could be clot abruption during stent retrieval into the smaller opening of a standard distal access catheter, and antegrade blood flow via collaterals despite proximal balloon protection. A funnel-shaped tip with a larger internal diameter was developed to increase the rate of first-pass recanalization and to improve the safety and efficacy of mechanical thrombectomy. - Methods - This in vitro study compared the efficacy of a funnel-shaped tip with a standard tip in combination with different clot compositions. Mechanical thrombectomy was performed 80 times for each tip, using two stent retrievers (Trevo XP ProVue 3/20 mm, 4/20 mm) and four different clot types (hard vs. soft clots, 0-24h vs. 72h aged clots). - Results - Significantly higher first-pass recanalization rates (mTICI 3) were observed for the funnel-shaped tip, 70.0% versus 30.0% for the standard tip (absolute difference, 32; relative difference 57.1%; P < .001), regardless of the clot type and stent retriever. Recanalization could be increased using harder Chandler loop clots versus softer statically generated clots, as well as 0-24h versus 72h aged clots, respectively. - Conclusion - The funnel-shaped tip achieved higher first-pass recanalization rates than the smaller standard tip and lower rates of clot abruption at the tip. Clot compositions and aging times impacted recanalization rates.
Erstmals online veröffentlicht: 1. September 2022
Gesehen am 16.07.2024